QBQ! : the question behind the question : practicing personal accountability in work and in life - Miller, John G., 1958- (New York : G. P. Putnam's Sons, 2004)
Presents a practical method, based on the QBQ (Question Behind the Question) tool, for putting personal accountability into daily action while avoiding blame, complaining and procrastination.
Originally published: Denver, CO : Denver Press, c2001.
Keywords: Choice (Psychology); Decision making; Problem solving; Responsibility